Penetration of ceftriaxone (1 or 2 grams intravenously) into mediastinal and cardiac tissues in humans. - Martin, C (1996)
Penetration of ceftriaxone into heart tissues (valves, myocardium, auricles, and pericardium) and mediastinal tissues (fat and sternal bone) was evaluated after two regimens of ceftriaxone administration. Ten patients (group 1) were given 1,000 mg of ceftriaxone intravenously 30 min before anesthesia. Ten other patients (group 2) received the same dose and then a second 1,000-mg dose at the time of initiation of cardiopulmonary bypass. Similar and very satisfactory penetrations of ceftriaxone into tissue were observed for both groups. During opening and closure of the thorax, mean ceftriaxone concentration was in excess of the MIC at which 90% of the potential pathogens were inhibited (> or = 4 micrograms/g) in the thoracic fat, the sternal bone, and the pericardium. No significant differences between the two administration regimens in penetration of ceftriaxone into tissue were observed. During cardiopulmonary bypass, the ceftriaxone concentration was > or = 4 micrograms/g in the myocardium, the endocardium, and the auricle. The regimen of ceftriaxone administration did not significantly influence penetration of the drug into heart tissues. However, for some patients in the two groups and mainly in the sternal bone at the time of thorax closure (6 patients in group 1 and 5 patients in group 2), ceftriaxone levels in tissues were less than the MICs (4 micrograms/g) for some potential pathogens (methicillin-susceptible Staphylococcus aureus and methicillin-susceptible Staphylococcus epidermidis). During the different steps of the surgical procedures, all (10 of 10) patients in each group had tissue ceftriaxone levels greater than the MICs for gram-negative aerobic bacilli (0.1 microgram/g), except for Pseudomonas spp.